Manchuria : : General situation - Great Britain Embassy (Japan); Great Britain Foreign Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1929)
Foreign Office file containing correspondence and memoranda relating to the political situation in Manchuria, Japanese trade with China and intentions towards Manchuria in the lead up to the Mukden Incident in 1931